FRI0147 PREVALENCE OF COMORBIDITIES IN ANTIPHOSPHOLIPID SYNDROME VERSUS RHEUMATOID ARTHRITIS: A MULTICENTRE, AGE- AND SEX-MATCHED STUDY. (2nd June 2020) - Panopoulos, S.; Thomas, K.; Georgiopoulos, G.; Boumpas, D.; Katsiari, C.; Bertsias, G.; Drosos, A.; Boki, K.; Dimitroulas, T.; Garyfallos, A.; Papagoras, C.; Katsimpri, P.; et al.
Abstract : Background: Comorbidities in rheumatic diseases (RDs) have been associated with increased morbidity and mortality. Evidence on prevalence of comorbidities in antiphospholipid syndrome (APS) and its difference from high comorbidity burden RDs is limited. Objectives: To compare the prevalence of common comorbidities between APS [primary (PAPS) and Systemic lupus erythematosus (SLE)-APS] and Rheumatoid arthritis (RA) patients. Methods: 326 APS patients from the Greek registry (237 women, mean age 48.7±13.4 years, 161 PAPS) were matched 1:2 for age and sex with 652 RA patients from Greek RA Registry. Prevalence of cardiovascular (CV) risk factors, stroke, coronary artery disease (CAD), osteoporosis, diabetes mellitus (DM), Chronic obstructive pulmonary disease (COPD), depression and neoplasms were compared between APS and RA using logistic regression analysis. Results: Regarding CV burden, hyperlipidemia and obesity (ΒMI≥30) were comparable while hypertension, smoking, CAD and stroke were more prevalent in APS compared to RA patients (Table 1 ). Osteoporosis and depression were more frequent in APS while DM, COPD and neoplasms were comparable between two groups. Comparison of APS subgroups to 1:2 matched RA patients revealed that smoking and stroke were more prevalent in PAPS and SLE-APS vs RA. Hypertension, CAD and osteoporosis were more prevalent only in SLE-APS vs. RA while DM was less prevalent in PAPS vs. RA patients. Conclusion: Comorbidity burden in APS (PAPS and SLE-APS) is comparable or even higher to that in RA, entailing a high level of diligence for CV risk prevention, awareness for depression and corticosteroid exposure minimization. Disclosure of Interests: Stylianos Panopoulos: None declared, Konstantinos Thomas: None declared, Georgios Georgiopoulos: None declared, Dimitrios Boumpas Grant/research support from: Unrestricted grant support from various pharmaceutical companies, Christina Katsiari: None declared, George Bertsias Grant/research support from: GSK, Consultant of: Novartis, Alexandros Drosos: None declared, Kyriaki Boki: None declared, Theodoros Dimitroulas: None declared, Alexandros Garyfallos Grant/research support from: MSD, Aenorasis SA, Speakers bureau: MSD, Novartis, gsk, Charalambos Papagoras: None declared, PELAGIA KATSIMPRI: None declared, Apostolos Tziortziotis: None declared, Christina Adamichou: None declared, Evripidis Kaltsonoudis: None declared, Evangelia Argyriou: None declared, GEORGIOS VOSVOTEKAS Grant/research support from: MSD, Janssen, Consultant of: MSD, Novartis, Roche, UCB pharma, Bristol-Myers Squibb, AbbVie, Speakers bureau: UCB pharma, Menarini, Bristol-Myers Squibb, MSD, Petros Sfikakis Grant/research support from: Grant/research support from Abvie, Novartis, MSD, Actelion, Amgen, Pfizer, Janssen Pharmaceutical, UCB, Dimitrios Vassilopoulos: None declared, Maria Tektonidou Grant/research support from: AbbVie, MSD, Novartis and Pfizer, Consultant of: AbbVie, MSD, Novartis and Pfizer